Iron-Doped Lithium Tantalate Thin Films Deposited by Magnetron Sputtering: A Study of the Iron Role in the Structure and the Derived Magnetic Properties - Farias, Rurik (2020)
Fe-doped LiTaO 3 thin films with a low and high Fe concentration (labeled as LTO: Fe-LC and LTO: Fe-HC, respectively) were deposited by magnetron sputtering from two home-made targets. The dopant directly influenced the crystalline structure of the LiTaO 3 thin films, causing the contraction of the unit cell, which was related to the incorporation of Fe 3+ ions into the LiTaO 3 structure, which occupied Li positions. This substitution was corroborated by Raman spectroscopy, where the bands associated with Li-O bonds broadened in the spectra of the samples. Magnetic hysteresis loops, zero-field cooling curves, and field cooling curves were obtained in a vibrating sample magnetometer. The LTO: Fe-HC sample demonstrates superparamagnetic behavior with a blocking temperature of 100 K, mainly associated with the appearance of Fe clusters in the thin film. On the other hand, a room temperature ferromagnetic behavior was found in the LTO: Fe-LC layer where saturation magnetization (3.80 kAm− 1) and magnetic coercivities were not temperature-dependent. Moreover, the crystallinity and morphology of the samples were evaluated by X-ray diffraction and scanning electron microscopy, respectively.